Analysis of Infrastructural Challenges in Efforts to Improve Healthcare Quality in Curug Village, Pandeglang Regency - Syah, Jelica Maulidna Adhelyn; Nabila, Fatma; Yanti, Luthfyna; Sijabat, Saut Gracer (KnE Social Sciences, 2025)
This research aims to analyze the strategies that can be implemented to address infrastructure challenges in efforts to improve health quality in Curug Village. The method used is qualitative, with data collected through interviews and documentation to gain in-depth insights into the situation. The results of the study indicate that Curug Village in Cibaliung District, Pandeglang Regency, faces significant challenges in infrastructural development and healthcare services due to limited accessibility and poor infrastructure. The poor road conditions severely restrict access to the village, affecting various aspects of community life, including health. Health-related challenges include the community’s limited knowledge, a preference for alternative medicine, and the lack of adherence to Clean and Healthy Living Behavior (PHBS). Healthcare services at the Cibaliung Community Health Center (Puskesmas) are also inadequate, with the number of healthcare workers being far below the ideal standard contributing to the high maternal and infant mortality rates. Various health programs have been initiated, including the Mobile Health Center (Puskesmas Keliling) program, but their effectiveness remains hindered by infrastructure issues and social resistance. To address these issues, the planning, organizing, actuating, and controlling (POAC) method is recommended, involving infrastructure improvements, capacity building for healthcare workers, continuous health education, and enhanced coordination among stakeholders, with a focus on optimizing the use of village funds to improve access and quality of healthcare services.